Mitigating Investment Irrationality in the Digital Era: Financial Education as a Strategic Moderator of Cognitive Bias and Social Media Influence - Risma Puspita Sari; I Gusti Ketut Agung Ulupui; Agung Dharmawan Buchdadi (Journal of Strategic Innovation in Economics and Business, 2026)
This study examines how cognitive biases and social media exposure influence investment decision-making among Millennials and Generation Z in Indonesia, while considering financial education as a moderating factor. Drawing on behavioral finance theory, this research examines how psychological and digital information factors shape investment behavior in an emerging market context. Data were obtained from an online survey involving 253 young investors and were analyzed using the Partial Least Squares–Structural Equation Modeling (PLS-SEM) approach. The results indicate that cognitive biases, particularly overconfidence and herding behavior, exert a significant influence on individual investment decisions. Social media exposure also significantly affects investment behavior, underscoring digital platforms as dominant sources of financial information for young investors. Furthermore, the findings reveal that financial education serves as an effective moderating mechanism in the relationships between cognitive biases and investment decisions, as well as between social media influence and investment decision-making. Higher levels of financial education help mitigate the adverse effects of psychological biases and reduce investors’ reliance on unverified financial information circulating on social media. These findings contribute to the behavioral finance literature by integrating cognitive bias, social media influence, and financial education within a unified empirical framework. From a practical standpoint, this study emphasizes the strategic importance of strengthening financial education initiatives to enhance the quality investment decisions among digitally native generations in emerging markets.